Perilaku Ekonomi Rumah Tangga Petani Dalam Peremajaan Kelapa Sawit Di Kampung Selamat Kecamatan Tenggulun Kabupaten Aceh Tamiang - Indah Syafira Lesmana; Faoeza Hafiz Saragih; M. Jamil (Universitas Wahid Hasyim, 2025)
This research aims to analyze the decision of farmers in Kampung Selamat towards replanting and to determine the economic ability of farmer households to carry out oil palm replanting to the household economy of farmers in Kampung Selamat, Tenggulun District, Aceh Tamiang Regency. The method used in this research is a qualitative method, namely this research is conducted field observations by interviewing oil palm farmers who have replanted using a questionnaire, then described clearly. The research method used in this study was obtained by recalling data through surveys. The sample taken in this study was 23 done by simple randomization. There are 2 data analysis techniques used, namely decision analysis and ability analysis. The results of this study are the decision of farmers in Kampung Selamat on oil palm replanting is influenced by the reasons that allegedly encourage the decision to